1996
DOI: 10.1063/1.363480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapid thermal anneal on refractive index and hydrogen content of plasma-enhanced chemical vapor deposited silicon nitride films

Abstract: Effect of ion energy on the optical and structural properties of SiO2 grown by plasmaenhanced chemicalvapor deposition LPCVD siliconrich silicon nitride films for applications in micromechanics, studied with statistical experimental design*

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 17 publications
5
19
0
Order By: Relevance
“…The optical gap E g of the N-rich films increases slightly unlike the Si-rich films; it decreases and approaches that of amorphous silicon a-Si. These experimental findings, confirmed by reflectivity measurements, are consistent with the results of some authors [21] [22]. This is can be correlated to the change of the structural properties as result of local rearrangement of the Si-H, N-H bonds following a densification of the N-rich SiN x films and a high outdiffusion rate of hydrogen for the Si-rich films.…”
Section: Optical Propertiessupporting
confidence: 92%
See 2 more Smart Citations
“…The optical gap E g of the N-rich films increases slightly unlike the Si-rich films; it decreases and approaches that of amorphous silicon a-Si. These experimental findings, confirmed by reflectivity measurements, are consistent with the results of some authors [21] [22]. This is can be correlated to the change of the structural properties as result of local rearrangement of the Si-H, N-H bonds following a densification of the N-rich SiN x films and a high outdiffusion rate of hydrogen for the Si-rich films.…”
Section: Optical Propertiessupporting
confidence: 92%
“…Michael et al [25] reported an increase in the hydrogen content with an increasing x of SiN x films deposited using a mixture of SiH 4 /N 2 /H 2 gas. Lauinger et al [26] reported that [H] remains at about ~10 22 cm −3 and does not follow any particular change with the stoichiometry of the film. In general, the difference in hydrogen content is attributed to the differences in bonds densities [Si-H] and [N-H].…”
Section: Structural Properties: Rbs Erda Infrared Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have been devoted to elucidate the underlying mechanisms of surface and bulk passivation of Si solar cells as induced by a-SiN x :H. [6][7][8][9][10][11][12][13][14][15][16][17][18] Bulk passivation can be achieved by a short high-temperature step, the socalled firing process, which is used for the application of screen-printed metallization of a-SiN x :H coated mc-Si solar cells. During this firing process, defect passivation in Si is obtained by hydrogen species that are released from the a-SiN x :H film and that diffuse into Si.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Furthermore, vacancy-hydrogen complex generation and Alenhanced void generation have been suggested to occur dur- ing the firing process of screen-printed Al-based contacts. [12][13][14][15][16] Furthermore, the retention of the atomic hydrogen at defect sites during the rapid cooling of the cells immediately after the firing process to obtain enhanced passivation effects has been considered. 15,16 An important issue for the application of a-SiN x :H films in the photovoltaic industry is the deposition rate of the a-SiN x :H. Increasing the deposition rate is a real challenge in large-scale solar cell production because at higher deposition rates investments in equipment can be kept relatively low reducing the costs per wafer processed.…”
Section: Introductionmentioning
confidence: 99%